Mastering Mandarin endocentric phrases: a five-step technique / Mok Soon Sim, S. Suchithra K.Sankaran and Lau Suk Khin - Mok, Soon Sim; K.Sankaran, S. Suchithra; Lau, Suk Khin (Akademi Pengajian Bahasa, 2019)
Mandarin Endocentric Phrases (MEP) is a type of Mandarin phrase which is classified according to its internal structure. It is formed by two components which share a [modifier-head word] relationship. The modifier component pre cedes the head word it modifies. The role of the modifier is to describe or limit the head word. The Five-Step Technique is a simplified method of arranging words to form MEP. It helps non-native speakers to master the process of sequencing MEP. This technique is informed by findings from research on error analysis in the use of MEP among Malay students in Universiti Teknologi MARA (UiTM) Shah Alam campus in 2019. UiTM Malay students are influenced by their mother tongue which is the Malay language when they learn the MEP, thus they often make mistakes in the construction and translation of MEP. This Five-Step technique delineates the correct sequence of MEP into five parts, starting from the demonstrative pronouns, followed by the measure word, modifier or adjective, particle “de” and finally the noun or object. This technique will enable students to produce error-free MEPs and instinctively build their motivation to master the language. Ideally, Mandarin teachers can use this innovative teaching approach to create an interactive and collaborative learning partnership in the Mandarin classroom.